Assessment of the Effect of Telephonic Follow-up on Readmissions and Mortality Rate of the Patients with Acute Coronary Syndrome and Acute Heart Failure in Rashid Hospital - Mary Sumitha Prabakaran; Naser Jamil; Rose Mary Thomas; Mayamol Mohanan; Anumol Jose; Akila Jeyasingh Chandrabose (Dubai Medical Journal, 2024)
Background: Acute coronary syndrome (ACS) and acute heart failure (AHF) are severe medical conditions that are closely associated with higher rates of readmissions and mortality in hospitals. These conditions pose an exponential challenge to the healthcare system and increase patient burden.